PENATAAN RUANG KAWASAN PEDESAAN BERBASIS PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN BENGKULU TENGAH - JT Pareke (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
The main of this research is the first to know and understand the space setting of farms areas in Central Bengkulu regency. The second is to know and understand the farmers’ rights covering for the farmlands in Central Bengkulu regency. The sample of this research is 10% people whose taken purposively from 16 villages who settled in Central Bengkulu regency. For this purpose, it was used empiric juridis approach, meanwhile the technique of collecting the data used was the literature review study and field study with using the instrument of structured interview, direct observation and questionnaire. The result of the research were, the first is the space setting of farm areas in Central Bengkulu regency is as the farm of space setting of centred village, where the people gathered in one place so all of facilities, whether settlement, public facilities, rice field and farm areas are centred. The second, the covering of farmers’ rights for the farm lands in Central Bengkulu regency is not sufficiently available, it was proved that there was none of villages as the sample which regulates the space setting of farm areas and the coverage of mers’ rights trough the intrument of village’s regulation